Problematika Cerai Ghoib dan Upaya Hukumnya - Eka Ristianawati (Syntax Corporation Indonesia, 2024)
The purpose of this study is to review what are the problems in ghoib divorce and how legal remedies can be taken by the defendant/respondent against the ghoib divorce decision. The type of research used is descriptive. This means that the research will be discussed in the form of a presentation that is elaborated carefully and thoroughly. In this case, the explanation of Ghoib's divorce begins with the conditions, summons, trials, and legal remedies against Ghoib's divorce decision. The result of this study is that, in the technical delivery of the summons, there may be mistakes or negligence on the part of the substitute bailiff, namely the summons is not delivered to the parties as usual. Second, there is a deliberate intention on the part of the husband (applicant) or plaintiff (wife) who deliberately conceals the address/identity of the Respondent or the defendant. Of course, this intentionality is based on the applicant's motive to escape from his rights and obligations after the divorce. The solution of the above two problems is the first: the court first summons the Respondent (wife) or Terggat (husband) to the last address or residence mentioned in the application before the Panel of Judges summons him through notice and the mass media. And the legal remedy if one of the parties objects to the result of Ghoib's divorce decision is to apply for a review.